Pentingnya Media Pembelajaran dalam Meningkatkan Minat dan Motivasi Belajar Siswa di SMP Negeri 2 Gunungsitoli Utara - Hiskia Ndraha; Agnes Renostini Harefa (Departement of Mathematics Education, 2023)
Learning is an activity between teachers and students in order to achieve learning objectives. The success or failure of achieving the learning objectives is determined by the teacher, because the teacher plays an active role in providing enthusiasm and growing students' desire to be enthusiastic in carrying out learning, a teacher must be able to guide students to be better in attitude, physically and also psychologically in participating in the learning process. The teacher's job is to provide knowledge and students are the recipients of that knowledge. Teaching and learning activities are activities of communicating knowledge to students and students act as recipients of the knowledge that has been taught by the teacher. This study aims to find out how important learning media is in increasing student interest and motivation in learning, where students sometimes feel bored with the learning methods used by teachers such as the lecture method, teachers demand more students to listen and understand the material presented by the teacher without expecting activeness students in participating in classroom learning, even though with the utilization of learning media students will be more active, innovative and creative. The research method used in this study was qualitative research with data collection instruments in the form of questionnaires and interview guides. Where the research subjects were students and teachers at SMP Negeri 2 Gunungsitoli Utara. By conducting this research we can conclude that in a learning activity that uses the media as an instrument that helps learning activities can create students who are characterized and active, innovative and creative and can be implemented in 3 things, among others in the educator, in the self educate and in teaching and learning.